Methodological and organizational aspects of newborn screening for congenital hypothyroidism in Macedonia - Gjurkova, Beti; Anastasovska, Violeta; Sukarova-Angelovska, Elena; Kocova, Mirjana (Macedonian Academy of Sciences and Arts, 2008)
Congenital hypothyroidism (CH) is the most common preventable cause of mental retardation. Early diagnosis and treatment are crucial to the prevention of severe intellectual deficit. Neonatal screening in a blood spot from the heel of the newborn between the 2nd and 5th day after birth and determination of thyroid stimulation hormone (TSH) level by fluoroimmunoassay (DELFIA method) is the commonly used approach for the timely detection and therapy of congenital hypothyroidism. Over the period April 2002 - December 2004 results of 27,782 samples were analysed. They were obtained from 5 hospitals in the Republic of Macedonia (Obstetrics and Gynaecology Clinic, Clinical Centre, Skopje; Cair Obstetrics and Gynaecology Hospital, Mala Bogorodica Hospital and hospitals within the cities of Bitola and Prilep). Over the period January 2005 - December 2007 the analysis of 50,732 samples covered all obstetrics hospitals in Macedonia. For the first period analysed (April 2002 - December 2004) we evaluated the sensitivity and specificity of the biochemical method applied for neonatal screening for CH. In our study TSH was assayed by DELFIA fluorometric kits. The cut-off value in our laboratory was 15 mU/L. We compared coverage, timeliness of programme indicators (age at sampling, recall and treatment initiation, timing of specimen delivery and laboratory results) and specimen quality with international standards. Recall rate, sensitivity, specificity, positive predictive values and relative incidence rate for CH were calculated. The established method was deemed highly sensitive and highly specific. During the period of analysis in our study, 28 cases were detected or an incidence rate of 1 : 2,804 was calculated. Treatment was initiated on the 13th day on average (between the 5th and 35th day).